Production and Transport of Supraglacial Debris: Insights From Cosmogenic 10Be and Numerical Modeling, Chhota Shigri Glacier, Indian Himalaya - Scherler, D.; Egholm, D. L. (2020)
Many mountain glaciers carry some amount of rocky debris on them, which modifies surface ablation rates. The debris is typically derived from erosion of the surrounding topography and its supraglacial extent is predominantly controlled by the relative accumulation rates of debris versus snow. Because Global Warming results in shrinking glaciers as well as thawing permafrost worldwide, changes in both rates will most likely affect the evolution of supraglacial debris cover and thus the response of glaciers to climate change. Here we report Be-10 concentrations measured in five amalgamated debris samples collected from the main medial moraine of the Chhota Shigri Glacier, India. Results suggest headwall erosion rates that are similar to 0.5-1 mm year(-1), and apparently increasing (Be-10 concentrations are decreasing) toward the present. We employed a numerical ice flow model that we combined with a new Lagrangian particle tracing routine to explore the impact of spatial and temporal variability in erosion rates and source areas on Be-10 concentrations in the medial moraine. Our modeling results show that neither changes in source areas, related to the transient response of the glacier to ongoing climate change, nor four different scenarios of spatial and temporal variability in erosion rates could explain the observed trend in Be-10 concentrations. Although not accounted for in our modeling explicitly, we suggest that the observed trend could be due to transiently enhanced erosion of recently deglaciated areas, or to greater spatial variability in erosion rates than explored in our models. High and steep mountain ranges are currently undergoing changes due to increasing temperatures. These changes include rapidly shrinking glaciers as well as thawing permafrost, which together destabilize rock walls that surround valley glaciers. In consequence, slope failures and thus erosion rates in these environments are expected to increase. However, quantifying rock wall erosion in alpine landscapes is difficult and ...